Evolução de pacientes portadores de peumopatias crônicas e hipoxemia transitória ao esforço tratados com oxigenoterapia domiciliar prolongada durante o sono e ao esforço - Mesquita, Carolina Bonfanti [UNESP] (2014)
Respiratory failure is usually present in clinical status of patients with advanced lung disease such as chronic obstructive pulmonary disease (COPD), interstitial lung disease (ILD) and pulmonary hypertension (PH). Long Term Oxygen Therapy (LTOT) as part of the treatment and is associated with control of disease progression and survival. However, there are little data in the literature about the effect of the LTOT in disease progression in patients with chronic lung diseases and exertional desaturation. Evaluate the influence of LTOT used during sleep and exertion in characteristics of patients with chronic lung diseases and exertional desaturation followed for one year. We evaluated 60 patients with COPD, 16 with ILD and 15 with PH. The exertional desaturation was confirmed by the six-minute walk test (6MWT) and the room air arterial blood gases. All patients received a recommendation to use 0.5 L/min during 12h/day of LTOT, including sleep and exertion periods. At baseline and after one year we assessed pulmonary pharmacological treatment, adherence to treatment, comorbidities by the Charlson index, body composition, spirometry, pulse oximetry (SpO2), arterial blood gas analysis, CBC, 6MWT supplemented with LTOT, Saint George Respiratory Questionnaire (SGRQ), dyspnea sensation according to baseline dyspnea index (BDI) and the Modified Medical Research Council (MMRC), score of anxiety and depression, frequency of exacerbation and mortality rate. We performed descriptive analysis of data comparing the moments of patients who presented stable exertional desaturation according to the group (COPD, ILD and PH patients). We compared groups according to the presence of stable exertional desaturation or severe hypoxemia and death. 39 patients with COPD, 11 with ILD and 11 with PH showed stable exertional desaturation. We observed that patients with stable exertional desaturation showed symptom improvement after one year, however, it was not ...